Performance of Hevea brasiliensis on Haplic Ferralsol as affected by different water regimes - Mokhatar, Shafar Jefri; Wan Daud, Wan Mohamed Noordin; Arbain, Nazera (Science Publications, 2011)
Problem statement: Rubber has been grown more than a century in South East Asia, who has been the largest producer of natural rubber. Demand of natural rubber increases steadily due to increasing demand particularly from developing countries. Water has been a limited and invaluable resource especially in agriculture. This resource has to be used wisely and there is a need for a detailed study pertaining to water requirement of rubber plants. This study provides details about rubber plants growth in relation to water stress. Approach: Two new latex timber clones from Malaysia Rubber Board (MRB), RRIM 2005 and RRIM 3001 were used in this study with soil from Haplic Ferralsol used as planting media. Five levels of treatment were used; plants irrigated for every 2, 5, 10 and 15days and everyday which acted as control. The experimental design used was a Completely Randomized Block Design (RCBD) with four replications. Results: Results showed treatment well watered for clone RRIM 2025 (T6) had most the turgidity with high mean value in stomata conductance and chlorophyll content. RRIM 2025 also more resist to water stress compared to RRIM 3001. All plants in treatments with extreme different in water regimes cannot survive and dead due to severe stress. Conclusion: This study found rubber clones RRIM 2025 and RRIM 3001 cannot survive with acute deficiency of water. Rubber cannot be planted in dry areas with low water regimes which will retard the plant growth and plant will die under severe water stress.